TIDAK SEKEDAR BERCERITA : Konsep Al-Hikâyah Sebagai Metode Pembelajaran Agama Islam - Harahap, Radinal Mukhtar (Turats, 2024)
This study examines al-hikâyah in Islamic religious learning. Although this practice overlaps with qissah and storytelling, it has its own unique character because it is considered as character building and educational ideal formation. This study is constructed by giving priority to stories as a learning tradition in Islam, so as to provide a fundamental view that stories, descriptions or a wealth of vocabulary and expressions are something special that emerges from the Islamic educational environment. Then, the argument is put forward that the teacher is the central figure in the organization of education, without whose authority simultaneous, continuous and sustainable education would not take place from time to time. In this section, it is argued that the ability to tell stories is a skill that a teacher, who is charged with character building or transmitting educational ideals, should possess. The final section discusses the implementation of al-hikâyah as a method of character formation and pedagogical idealism and transforms the ability to teach it effectively into a teacher competence that can be further optimized from time to time.